PERILAKU KONSUMTIF GENERASI Z: PERAN LITERASI KEUANGAN DAN PENDAPATAN DI KOTA BOGOR - Neng Revi Anugrah; Erny Amriani Asmin; Titiek Tjahja Andari (Universitas Dharmawangsa, 2026)
The purpose of this study is to determine the influence of financial literacy and income on the consumptive behavior of Generation Z in Bogor City.This study employed quantitative research. Data were collected using a Likert-scale questionnaire from 384 Generation Z respondents residing in Bogor City. This study employed regression analysis with SPSS 27 software. The results indicate that financial literacy and income have a positive and significant influence on the consumptive behavior of Generation Z in Bogor City.